ANALISIS PERFORMA WEBSITE SCLEAN MENGGUNAKAN PINGDOM TOOLS DAN PAGE SPEED INSIGHTS - Stefany Yason; Sudirman; Arfan Yunus (KHARISMA Tech, 2022)
: Team Nucom launched the SClean laundry application to provide services and facilitators for laundry service users. The SClean application can provide service and services to customers who need laundry sevice online through online access to overcome obstacles to washing clothes on time. SClean can be accessed via this link “https://sclean.org/” using a smarthphone via a browser and also directly download the application via this Playstore. Tested on the SClean website using pingdom tools and page speed insights to collect data results that can be analyzed in terms of speed and performance measurements. The test results using pingdom tools are 80 while using page speed insights are 98.